- #1

recoil33

- 28

- 0

1.

y = (5x+2)

^{2}/((x+5)

^{3})

^{2}

u = (5x+2)

^{2}

u' = 7(5x+3)

^{6}. (5)

v = (x+5)

^{3}

v' = (3(x+5)

^{2}).(1)

Quotient = (u(x)*v'(x) - v(x)* u'(x) / v(x)

^{2})

(5x+2)

^{7}. 3(x+5)

^{2}- (x+5)

^{3}. 7(5x+5)

^{6}.(5) / ((x+5)

^{3})

^{2}

[ If i knew how to put this under i would ]

What have i done wrong here? not exactly sure ;s

__________________________________________________________________________

2.

If i have an equation with 2 brackets on the numerator, and only 1 on the denominator will i use the product rule for the numerator then the quotient? Or, will i expand the brackets then use the quotient rule?

Example:

(4x+9)(6x+1) / (8x+3)

u = (4x+9)(6x+1)

u' = (4x+9)(6) + (6x+1)(4)

v = (8x+3)

v' = (8)

Am i doing the right thing here? Any advice will help thank you.

[If my question is not clear please tell me]

Thanks in advance, recoil33